A Potential Protective Effect of Alcohol Consumption in Male Genital Lichen Sclerosus: A Case-Control Study - Joey El Khoury; Jessica Andraos; Anthony Kanbar; Rami Halabi; Serge Assaf; Anthony Mina; Sabine El Breidi; Charbel Dabal; Charbel El Hachem; Rodrigue Saad; Antoine Kassis; Maher Abdessater; et al. (Advances in Urology)
Introduction and Objectives. Lichen sclerosus (LSc) is a chronic inflammatory process of the skin characterized by its unique histological features. It affects men and women of all ages, mainly in the anogenital area. The etiologies and exact pathophysiology are not well-known; however, LSc can be considered a precursor to male genital squamous cell carcinoma. We aim, through this case-control study, to potentially associate genital LSc with risk factors and certain patient characteristics in Lebanese adult males. Materials and Methods. A nested case-control study design was chosen. Subjects enrolled were adult male patients who had a circumcision between January 2010 and December 2020 at our university hospital, with a confirmed LSc diagnosis on pathology. Cases were matched with controls by age with a ratio of 1 : 1, all of whom were circumcised and had a negative pathology report. Data collection consisted of sociodemographic, behavioral, and past medical and familial history characteristics. Results. A total of 94 patients were enrolled. The mean age was 49.81 (±22.92) in the group of men with LSc. No significant differences in sociodemographic characteristics (age and BMI) were found between the two compared groups. Smoking cannot predict LSc as opposed to alcohol consumption, which we found to be a protective factor against the appearance of LSc (p=0.027). Men with LSc had significantly higher rates of diabetes (p=0.021) and hypertension (p=0.004). No associations were found between LSc and the presenting chief complaints, family history of LSc, and past penile trauma. Conclusion. In this study, we were able to compare multiple variables between 47 circumcised patients diagnosed with LSc and a control group. We found that LSc patients showed higher rates of diabetes and hypertension. A potential protective effect of alcohol consumption is to be explored in future projects with bigger sample sizes and higher statistical powers.